1999
DOI: 10.1246/bcsj.72.603
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalysis of New Generation Chiral Metallosalen Complexes

Abstract: Chiral metallosalen complexes have been recognized as one of the most promising catalysts for various asymmetric reactions. The studies on asymmetric epoxidation catalyzed by chiral (salen)manganese complexes will be reviewed at first. The enantioselectivities have reached to the level as high as 90—99% ee for the epoxidation of conjugated cis-di- and trisubstituted olefins by developing the second generation of chiral salen ligands. Although it has been proven by Freichtinger and Plattner that epoxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(87 citation statements)
references
References 68 publications
0
77
0
10
Order By: Relevance
“…It has already been demonstrated that the oligo(salamo) helical complexes show unique physical properties and reactivities [98][99][100][101], and the dynamic helicity control would be useful for switching of the chiroptical properties of the helical structures. The catalytic reactivity of the chiral metallosalen scaffold [84][85][86][87] could also be incorporated into the oligo(salamo) helical structures, which could dynamically switch the enantioselectivity of the catalytic reactions. In this sense, the oligo(salen)-type helical structures are promising to provide an excellent platform that can drive the dynamic switching of various kinds of chiral functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that the oligo(salamo) helical complexes show unique physical properties and reactivities [98][99][100][101], and the dynamic helicity control would be useful for switching of the chiroptical properties of the helical structures. The catalytic reactivity of the chiral metallosalen scaffold [84][85][86][87] could also be incorporated into the oligo(salamo) helical structures, which could dynamically switch the enantioselectivity of the catalytic reactions. In this sense, the oligo(salen)-type helical structures are promising to provide an excellent platform that can drive the dynamic switching of various kinds of chiral functions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to control the helicity in a more rational and predictable fashion, we focused on chiral salen derivatives, which have two chiral carbon centers at the ethylene bridge of the salen ligands. It is well known that some chiral salen complexes act as excellent enantioselective catalysts (up to 99% ee) [84][85][86][87] and this indicates that the chiral twist is perfectly controlled in these systems. The chiral twist can be discussed in terms of the N-C-C-N dihedral angles (+60 deg or −60 deg) of the ethylene bridge in the salen ligands.…”
Section: Strategymentioning
confidence: 93%
“…Many mixed ligand complexes possess significant biological activities such as antibacterial [2,3], antimicrobial [4,5], anticancer [6] and antitumor [7]. Further, chiral mixed ligand complexes also used as catalysts in various important chemical transformations like epoxidation [8], resolution of racemic compounds [9] and other asymmetric synthesis [10,11]. In addition to these, some mixed ligand complexes also have potential applications in advanced materials such as semiconductors [12], magnetic [13] and non-linear optical materials [14].…”
Section: Introductionmentioning
confidence: 99%
“…The utility aspects of these complexes have received their share of attention as these have found applications in diverse fields. Chiral metal complexes are well known for their use as catalysts, especially in asymmetric synthesis [1][2][3] , asymmetric epoxidations or Sharpless epoxidations 4 and resolution of racemic compounds 5 . Light catalyzed inversion and diastereoisomeric equilibration 6 in chiral metal complexes have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%